Civil Society: Pembangun dan Sekaligus Perusak Demokrasi - Hadiwinata, Bob Sugeng (Jurnal Ilmu Sosial dan Ilmu Politik, 2005)
Disillusions with the limits of parliamentary politics and the increasingly dilapidated processes of party politics have generated a renewed interest on civil society as a means of rejuvenating public life. In light of mounting animosity against the "high politics" of political parties, parliament, and constitution, civil society is perceived as the diagnosis as well as cure for current ills in politics. This led to glorification of civil society as an alternative to conventional practice of politics. However, experience from new democracies suggests that civil society has been increasingly tampered with cranks, extremists, rejectionists, and crooks. This paper attempts to present two faces of civil society: civil and uncivil; and tries to relate them to democratization. Drawing on Indonesian experience, it argues that civil society can be both supportive and destructive to democracy.